Pharmacological Evaluation of Daidzein-loaded Solid Lipid Nanoparticle Gel for Anti-inflammatory Effect in Experimental Animals (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Daidzein (4′,7-dihydroxylisoflavone) is one of the major isoflavone present in various Leguminosae plant including Soybeans in higher percentage. Daidzein has been reported by various researchers for wide application in management of inflammatory diseases. The objective of present research work was to evaluate Daidzein loaded solid lipid nanoparticle (DAID–SLNs) gel for anti-inflammatory effectiveness in both acute and chronic inflammatory models, such as rat paw edema induced by carrageenan and granuloma induced by cotton pellets. Anti-inflammatory effects were observed by measurement of paw edema at different time interval, level of pro-inflammatory markers, granuloma weight and histological study of granuloma tissue. Results of the study were showed Daidzein loaded SLNs gel was gradually increases up to 180 min with increase in percent inhibition of edema. DAID–SLNs gel was showed significant (P<0.05) effects in chronic inflammatory tests with reduced cotton pellet-induced granuloma weight in comparison to control group and was comparable to market formulation Voltaren Emulgel. The anti-inflammatory effect was supported by significant (P<0.05) attenuation of TNF-α (44.20±1.55), IL-6 (35.28±2.04), and PGE2 (48.24±2.54) in comparison to the control group. In addition, effect was supported by histological observation with many blood vessels that are growing and fewer acute inflammatory cells and lymphocytes. In conclusion, anti-inflammatory effect of Daidzein was observed by decreasing the exudate, granuloma weight, and inflammatory markers. The possible mechanisms could be the inhibitory effect on prostaglandins biosynthesis and expression of the inflammatory cytokines.